SOUND OF AFRICA SERIES. LP (33 1/3 r.p.m.), 12 in. records. The International Library of African Music, P.O. Box 138, Roodepoort, nr. Johannesburg, South Africa (International Library of African Music, 1959)
pages: 96-97
Keywords: South Africa; African Music